2013
DOI: 10.3389/fendo.2013.00185
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence that 2D:4D is Related to the Number of CAG Repeats in the Androgen Receptor Gene

Abstract: The length ratio of the second to the fourth digit (2D:4D) is a putative marker of prenatal testosterone (T) effects. The number of CAG repeats (CAGn) in the AR gene is negatively correlated with T sensitivity in vitro. Results regarding the relationship between 2D:4D and CAGn are mixed but have featured prominently in arguments for and against the validity of 2D:4D. Here, I present random-effects meta-analyses on 14 relevant samples with altogether 1904 subjects. Results were homogeneous across studies. Even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Similarly, more direct evidence shows that 2D:4D strongly predicts the effects of T administration on empathy and cooperation in women [32,33]. These findings suggest that 2D:4D is a putative marker for sensitivity to T, although attempts to show that 2D:4D correlates with the androgen receptor gene have been inconclusive [34].…”
Section: Tablementioning
confidence: 94%
“…Similarly, more direct evidence shows that 2D:4D strongly predicts the effects of T administration on empathy and cooperation in women [32,33]. These findings suggest that 2D:4D is a putative marker for sensitivity to T, although attempts to show that 2D:4D correlates with the androgen receptor gene have been inconclusive [34].…”
Section: Tablementioning
confidence: 94%
“…For a long time, the relationship between AR (CAG)n and the ratio has been used as the index in assessing the effect of fetal testosterone level on 2D:4D (Manning, Bundred, Newton, & Flanagan, ). Unfortunately, two early meta‐analyses indicated that AR (CAG)n is not significantly associated with the ratio (Hönekopp, ; Voracek, ). However, the conclusion from the meta‐analyses were not supported by the subsequent studies with new samples (Durdiaková et al, ; Durdiaková, Celec, Laznibatova, Minarik, & Ostatnikova, ; Warrington et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The skeletogenic genes, some 20 in number, have multiple additional functions, which include the morphogenesis of the reproductive organs and the brain (Zheng and Cohn, ; Lawrance‐Owen et al, ). However, no firm links between variants of the AR and (postnatal) 2D:4D have been identified in humans (Hönekopp, ; Voracek, ) or zebra finches (Forstmeier et al, ), although a relationship with the ER‐α in zebra finches has been shown (Forstmeier et al, ). In humans, van Honk et al have reported that 2D:4D strongly moderates the influence of experimentally administered exogenous testosterone on empathy (van Honk et al, ), co‐operation (van Honk et al, ), and moral judgments (Montoya et al, ) in women.…”
mentioning
confidence: 99%